The Harm of Metabolically Healthy Obese and the Effect of Exercise on Their Health Promotion - Su, Liqiang; Pan, Yihe; Chen, Haichun (Frontiers in Physiology, 2022)
Obesity and obesity-related diseases (type 2 diabetes, cardiovascular disease [CVD], and cancer) are becoming more common, which is a major public health concern. At present, there is a wide consensus on the “obesity paradox.” Metabolically healthy obesity (MHO) is still harmful to health. It was discovered that MHO screening criteria could not well reflect health hazards, whereas visceral fat, adiponectin pathway, oxidative stress, chronic inflammation, and histological indicators at the microlevel could clearly distinguish MHO from health control, and the biological pathways involved in these micro indicators were related to MHO pathogenesis. This review reveals that MHO’s micro metabolic abnormality is the initial cause of the increase of disease risk in the future. Exploring the biological pathway of MHO is important in order to develop an effective mechanism-based preventive and treatment intervention strategy. Exercise can correct the abnormal micro metabolic pathway of MHO, regulate metabolic homeostasis, and enhance metabolic flexibility. It is a supplementary or possible alternative to the traditional healthcare prevention/treatment strategy as well as an important strategy for reducing MHO-related health hazards.